Mobilisation and remobilisation of a large archetypal pathogenicity island of uropathogenic Escherichia coli in vitro support the role of conjugation for horizontal transfer of genomic islands - Schneider, György; Dobrindt, Ulrich; Middendorf, Barbara; Hochhut, Bianca; Szijártó, Valéria; Emody, Levente; Hacker, Jörg (BMC microbiology, 2011)
A substantial amount of data has been accumulated supporting the important role of genomic islands (GEIs)--including pathogenicity islands (PAIs)--in bacterial genome plasticity and the evolution of bacterial pathogens. Their instability and the high level sequence similarity of different (partial) islands suggest an exchange of PAIs between strains of the same or even different bacterial species by horizontal gene transfer (HGT). Transfer events of archetypal large genomic islands of enterobacteria which often lack genes required for mobilisation or transfer have been rarely investigated so far. To study mobilisation of such large genomic regions in prototypic uropathogenic E. coli (UPEC) strain 536, PAI II536 was supplemented with the mobRP4 region, an origin of replication (oriVR6K), an origin of transfer (oriTRP4) and a chloramphenicol resistance selection marker. In the presence of helper plasmid RP4, conjugative transfer of the 107-kb PAI II536 construct occured from strain 536 into an E. coli K-12 recipient. In transconjugants, PAI II536 existed either as a cytoplasmic circular intermediate (CI) or integrated site-specifically into the recipient's chromosome at the leuX tRNA gene. This locus is the chromosomal integration site of PAI II536 in UPEC strain 536. From the E. coli K-12 recipient, the chromosomal PAI II536 construct as well as the CIs could be successfully remobilised and inserted into leuX in a PAI II536 deletion mutant of E. coli 536. Our results corroborate that mobilisation and conjugal transfer may contribute to evolution of bacterial pathogens through horizontal transfer of large chromosomal regions such as PAIs. Stabilisation of these mobile genetic elements in the bacterial chromosome result from selective loss of mobilisation and transfer functions of genomic islands.